2018
DOI: 10.1002/lary.27358
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient versus inpatient parotidectomy: Comparison of postoperative complication rates

Abstract: Objectives Parotidectomies have become a common outpatient procedure, but their impact on postoperative complications as compared to inpatient procedures has not been evaluated in a multi‐institutional study. Study Design The aim of this retrospective analysis was to evaluate the differences in outcomes using a standardized cohort of patients undergoing outpatient or inpatient parotidectomies. Methods The National Surgical Quality Improvement Program database was queried for parotidectomies between 2005 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 25 publications
3
41
1
Order By: Relevance
“…Herein, we present the largest national study examining the rate of 30‐day readmission after parotidectomy. In our analysis of 15,102 patients, the rate of readmission (3.9%) was greater than the published rates in large database analyses of the National Cancer Database (NCDB) by Zhan et al (2.1%) and the American College of Surgeons’ National Surgical Quality Improvement Program (ACS‐NSQIP) by Siddiqui et al (1.6%) . Both studies, however, likely underestimated the true readmission rate.…”
Section: Discussioncontrasting
confidence: 68%
“…Herein, we present the largest national study examining the rate of 30‐day readmission after parotidectomy. In our analysis of 15,102 patients, the rate of readmission (3.9%) was greater than the published rates in large database analyses of the National Cancer Database (NCDB) by Zhan et al (2.1%) and the American College of Surgeons’ National Surgical Quality Improvement Program (ACS‐NSQIP) by Siddiqui et al (1.6%) . Both studies, however, likely underestimated the true readmission rate.…”
Section: Discussioncontrasting
confidence: 68%
“…Two studies reported the specific histopathology of the final surgical specimen, and 2 studies reported only malignancy status. 7,10,14-16…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that one of the greatest expenses for surgical patients is length of time in hospital following surgery, which is prolonged in patients with surgical drains [ 14 , 32 , 33 ]. Given these findings, there has been increased interest in performing outpatient head and neck procedures, including parotid surgery [ 34 36 ]. A recent systematic review and meta-analysis by Flach et al [ 37 ] demonstrated that outpatient parotidectomy appeared to be safe with no increased risk of postoperative complications or readmission rates compared to inpatient procedures.…”
Section: Discussionmentioning
confidence: 99%